CCAFS site atlas – Khulna / Morrelganj - Sijmons, Koert; Kiplimo, Joyce; Förch, Wiebke; Thornton, Philip K.; Bhatta, Gopal Datt; Aggarwal, Pramod K. (2013)
CCAFS site atlas for Khulna / Morrelganj, Bangladesh.